2013
DOI: 10.2340/00015555-1564
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Topical Formulation Containing Strontium Chloride Significantly Reduces the Intensity and Duration of Cowhage-Induced Itch

Abstract: The aim of this double-blinded, vehicle-controlled study was to test the antipruritic efficacy of topical strontium to relieve a nonhistaminergic form of itch that would be clinically relevant for chronic pruritic diseases. Itch induced with cowhage is mediated by PAR2 receptors which are considered to play a major role in itch of atopic dermatitis and possibly other acute and chronic pruritic conditions. The topical strontium hydrogel formulation (TriCalm®) was tested in a head-to-head comparison with 2 commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…Topical strontium in a 4 % formulation was recently shown in one double-blind, vehicle-controlled trial to be effective in reducing both the duration and the peak intensity of experimentally induced itch in humans [137]. Strontium can be used therapeutically for itch secondary to xerosis, NE or LSC.…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…Topical strontium in a 4 % formulation was recently shown in one double-blind, vehicle-controlled trial to be effective in reducing both the duration and the peak intensity of experimentally induced itch in humans [137]. Strontium can be used therapeutically for itch secondary to xerosis, NE or LSC.…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…Papoiu et al . showed that the strontium chloride formulation was superior to hydrocortisone on the peak of skin itch intensity (32). So the strontium chloride was considered as positive control.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 56 healthy human volunteers (36 men and 20 women, aged 26-44 years) in 2 groups of 28 volunteers each were recruited and written consent was obtained from all subjects. Volunteers were factory workers recruited from the Goltash Company with a self-reported history of “sensitive skin” and were sensitive to a prescreening lactic acid facial challenge (32). The study protocol was approved by the Ethics Committee of Isfahan University of Medical Sciences (ID No: IR.MUI.REC.93.3.378).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical strontium gel, a calcimimetic that blocks ion channels in nerves, has been shown in a double-blind study to inhibit itch induced by cowhage and histamine and has been used against different types of chronic itch (Zhai et al 2000b;Papoiu et al 2013).…”
Section: Miscellaneous Ion Channel Blockersmentioning
confidence: 99%